2019
DOI: 10.3390/cancers11101535
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Characterization of Immune Cell Infiltrate and Expression of Immune Checkpoint Molecules PD-L1/CTLA-4 and MMR Proteins in Testicular Germ Cell Tumors Disclose Novel Disease Biomarkers

Abstract: Background: The immune infiltrate plays an important part in testicular germ cell tumors, but it remains scarcely studied. We aimed at thoroughly characterizing the immune infiltrate and expression of immune checkpoints PD-L1/CTLA-4 and mismatch repair (MMR) proteins in these neoplasms, seeking for associations with patient outcome. Methods: A total of 162 consecutively diagnosed patients (2005–2018) were included. Immunostaining for PD-L1, CTLA-4 and MMR proteins was independently assessed both in immune cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 66 publications
4
50
1
Order By: Relevance
“…Characterization of the immune infiltrate in terms of immune checkpoint PD-L1/CTLA-4 expression and its correlation with patient outcome was carried out by Lobo et al A predominant portion of 162 analyzed samples exhibited PD-L1 and CTLA-4 positivity in infiltrating immune cells (ICs) regardless of the histological subtype, while the expression of CTLA-4 in tumor cells (TCs) was significantly higher in yolk sac tumor, choriocarcinoma, and teratoma samples. The most frequent PD-L1 TC positivity was determined in choriocarcinomas (28). These results are in line with data from Sadigh et al, where choriocarcinoma was the only GCT histological subtype expressing PD-L1 in tumor cells, whereas other subtypes primarily expressed varying levels of PD-L1 on tumor-associated macrophages (TAMs) without true PD-L1 expression on tumor cells themselves.…”
Section: Rationale For Immunotherapy In Testicular Cancersupporting
confidence: 90%
See 1 more Smart Citation
“…Characterization of the immune infiltrate in terms of immune checkpoint PD-L1/CTLA-4 expression and its correlation with patient outcome was carried out by Lobo et al A predominant portion of 162 analyzed samples exhibited PD-L1 and CTLA-4 positivity in infiltrating immune cells (ICs) regardless of the histological subtype, while the expression of CTLA-4 in tumor cells (TCs) was significantly higher in yolk sac tumor, choriocarcinoma, and teratoma samples. The most frequent PD-L1 TC positivity was determined in choriocarcinomas (28). These results are in line with data from Sadigh et al, where choriocarcinoma was the only GCT histological subtype expressing PD-L1 in tumor cells, whereas other subtypes primarily expressed varying levels of PD-L1 on tumor-associated macrophages (TAMs) without true PD-L1 expression on tumor cells themselves.…”
Section: Rationale For Immunotherapy In Testicular Cancersupporting
confidence: 90%
“…In addition, a similar pattern was also determined for CTLA-4 immunoexpression in ICs. Namely, higher CTLA-4 expression correlated with good prognostic features, including lymphovascular invasion and lower pT and N stages (28). Moreover, Yamada et al showed the prognostic value of CD66b + tumor-infiltrating neutrophils (TINs) in 102 patients who underwent orchiectomy due to testicular cancer.…”
Section: Rationale For Immunotherapy In Testicular Cancermentioning
confidence: 99%
“…As the staining was overall diffuse in all cases, but with great variation in staining intensity, we focused on the latter. The intensity of staining was considered as “weak”, “moderate”, and “strong”, as previously defined [ 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…Both the intensity (0, 1, 2 and 3, corresponding to absent, weak, intermediate and strong staining) and percentage of stained tumor cells were assessed independently, as done in previous studies assessing these markers. "weak", "intermediate" and "strong" was defined as indicated in [28]. Overall assessment was reported for mixed tumors, since 17/23 consisted of tumors with > 90% embryonal carcinoma, with only small foci of cells from other distinct subtypes.…”
Section: Scoring Of Immunostainingsmentioning
confidence: 99%